OPTIMALISASI DIKMASLANTAS MELALUI SOSIALISASI TERTIB LALU LINTAS GUNA MEWUJUDKAN KAMSELTIBCARLANTAS DI WILAYAH HUKUM POLRES KUDUS - EGA SATYA NUGRAHA EGA SATYA NUGRAHA (Indonesian Journal of Police Studies, 2022)
ABSTRACT OPTIMIZATION OF DIKMASLANTAS THROUGH SOCIALIZATION OF TRAFFIC ORDER TO REALIZE KAMSELTIBCARLANTAS IN THE JURISDICTION OF POLRES KUDUS Ega Satya Nugraha, Academy No: 2018.128 Indonesian National Police Academy Email: egasn99@gmail.com Kudus City is one of the cities that has many factories, so many employees/private sectors use motorcycle for transportation to work. This of course has an impact on increasing traffic flow. The domination of the Kudus Regency population who work as employees/private sectors in traffic violations and accidents should certainly be the attention of the Kudus Police through the Traffic Unit to handle them. Many things have been done by the National Police in addressing and dealing with these problems through preemptive, preventive and repressive actions. One of the preemptive actions of the Kudus Police Unitkamsel is the traffic order socialization program which is carried out on a scheduled and periodic basis at factories/industries where employees/laborers work, with the hope of increasing literacy about the importance of orderly traffic. This research uses Management Theory, Optimization Theory, Socialization Theory, Traffic Order Concept, and Dikmaslantas Concept. The approach in this research is qualitative, using non-participant field research methods, as well as data collection by interview, observation, and document review.